2014
DOI: 10.1080/17518253.2014.922220
|View full text |Cite
|
Sign up to set email alerts
|

Long-chain double SO3H-functionalized Brønsted acidic ionic liquids catalyzed selective alkylation of phenol andp-cresol with tert-butanol

Abstract: A simple, efficient, and selective approach for the tert-butylation of phenol and p-cresol using two double SO 3 H-functionalized long-chain Brønsted acidic ionic liquids as recyclable catalysts is reported. Under optimum reaction conditions, 89.4% conversion of the phenol and 73.7% selectivity of 2,4-tert-butyl-phenol and 93.2% conversion of the p-cresol and 89.2% selectivity of 2-tert-butyl-p-cresol were obtained. Two ionic liquids could be recovered readily and their catalytic activity almost completely ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In addition, titania modified with a 12-tungstophosphoric acid (TPA/TiO 2 ) catalyst was prepared by Kumbar et al, and surface area, XRD, 31 P MAS NMR, XPS, NH 3 -TPD, and FTIR pyridine adsorption were employed to characterize these catalysts, and an 82% conversion of p-cresol and an 89.5 selectivity of 2-tert-butyl-p-cresol were obtained under the optimized reaction conditions [38]. Long-chain double SO 3 H-functionalized Brønsted acidic ionic liquids were synthesized, and the catalytic performances for the alkylation of p-cresol were investigated; an 89.4% conversion of the phenol, a 73.7% selectivity of 2,4-tert-butyl-phenol, a 93.2% conversion of p-cresol, and an 89.2% selectivity of 2-tert-butyl-p-cresol were obtained by Li et al [39]. Additionally, the alkylation of p-cresol with MTBE to synthesize 2-tert-butyl-pcresol was investigated, and a mesoporous and strong acid catalyst UDCaT-1 was prepared by Yadav et al The ratio of p-cresol and MTBE was 1:1; the reaction temperature was set as 100 • C, and a 45% conversion was obtained [40].…”
Section: Comparison Of Cal-tsoh With Other Catalystsmentioning
confidence: 99%
“…In addition, titania modified with a 12-tungstophosphoric acid (TPA/TiO 2 ) catalyst was prepared by Kumbar et al, and surface area, XRD, 31 P MAS NMR, XPS, NH 3 -TPD, and FTIR pyridine adsorption were employed to characterize these catalysts, and an 82% conversion of p-cresol and an 89.5 selectivity of 2-tert-butyl-p-cresol were obtained under the optimized reaction conditions [38]. Long-chain double SO 3 H-functionalized Brønsted acidic ionic liquids were synthesized, and the catalytic performances for the alkylation of p-cresol were investigated; an 89.4% conversion of the phenol, a 73.7% selectivity of 2,4-tert-butyl-phenol, a 93.2% conversion of p-cresol, and an 89.2% selectivity of 2-tert-butyl-p-cresol were obtained by Li et al [39]. Additionally, the alkylation of p-cresol with MTBE to synthesize 2-tert-butyl-pcresol was investigated, and a mesoporous and strong acid catalyst UDCaT-1 was prepared by Yadav et al The ratio of p-cresol and MTBE was 1:1; the reaction temperature was set as 100 • C, and a 45% conversion was obtained [40].…”
Section: Comparison Of Cal-tsoh With Other Catalystsmentioning
confidence: 99%
“…Alkylation of phenol (PhOH) with tert -butyl alcohol (TBA) to synthesize tert -butyl phenol is one of the most significant Friedel–Crafts reactions in the chemical industry . As an important raw material, tert -butyl phenol was usually used for the preparation of fine chemicals, ultraviolet absorbents, antioxidants, fuel stabilizers, agrochemicals, fungicides, heat stabilizers for polymers, dye intermediates, resins, and so on. According to reports, both homogeneous and heterogeneous catalysts were reported in the alkylation of PhOH and TBA, including Lewis acids (such as AlCl 3 and BF 3 ), Bronsted acids (such as HF, H 2 SO 4 , and H 3 PO 4 ), mesoporous materials, , cation-exchange resins, , heteropoly acids, and ionic liquids. However, the homogeneous catalysts, such as liquid acids, are unfriendly to environment and difficult to separate from the reaction system. Additionally, the corrosivity of homogeneous catalysts is also a difficult problem to solve.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Li et al reported a long-chain double SO 3 H-functionalized Brønsted acidic ionic liquid. A temperature of 70 °C was needed for the alkylation of PhOH with TBA in this report. Subsequently, a response surface methodology was employed to optimize the reaction conditions and the kinetic study was performed.…”
Section: Introductionmentioning
confidence: 99%